Forest regeneration and future stand trajectories following mountain pine beetle-caused lodgepole pine mortality - Pelz, Kristen A., author; Smith, Frederick W., advisor; Dickinson, Yvette L., committee member; Martin, Patrick H., committee member; Rhoades, Charles C., committee member (Colorado State University. Libraries, 2014)
A mountain pine beetle (MPB) (Dendroctonus ponderosae) outbreak that began in the late 1990s has killed lodgepole pine (Pinus contorta var. latifolia) on up to 10 million hectares in western North America. Over one million hectares have been affected in northern Colorado and southern Wyoming. The large footprint of this disturbance has prompted widespread concern about the composition, structure, and function of forests as they develop following MPB. In this dissertation, I ask how variation in species composition and mortality level will affect the future forest in the Southern Rockies. I used forest growth models to predict forest structure and fuel loads during the century after MPB outbreak. I compared three lodgepole pine-dominated forest types (all > 80 % lodgepole by basal area) and the simulated effects of no-action and fuel reduction treatments. Forest with Engelmann spruce (Picea engelmannii) and subalpine fir (Abies lasiocarpa var. lasiocarpa) became much more dominated by these species, resulting in highly hazardous canopy fuels. In contrast, stands of lodgepole and aspen (Populus tremuloides) did not shift composition and did not show a marked increase in fire hazard. The effects of management were also differed: hazardous fuels were best mitigated in the forest types with spruce and fir, but treatment had few positive effects in the stands of only lodgepole and aspen due to their lower hazard without treatment. The results show management of lodgepole-dominated forests must consider even subtle variation in composition to be effective. I also examined post-outbreak regeneration in these forests. In mixed lodgepole pine and aspen stands, I asked if regeneration is sufficient to reforest areas affected by MPB. Both species excel in high light environments that are created by overstory mortality, but lodgepole pine is thought to require ground disturbance to regenerate. Aspen regeneration can be prevented by browsing. I found lodgepole regeneration is occurring in 85% of stands, and all stands had aspen sucker density above 1000 stems ha-1. Many suckers are damaged by browsing, but my results suggest that sufficient quantities of down lodgepole pine may protect suckers and allow them to recruit to the overstory. Overall, I conclude aspen and lodgepole forests are regenerating successfully and that these areas will remain mixed forests of both species in the future. Finally, I measured the effects of mortality level on regeneration. I compared regeneration density and growth of lodgepole, spruce, and fir in high (85% of basal area) and moderate (40% of basal area) mortality forest. Lodgepole pine regeneration density and growth was high where outbreak was most severe, though all species grew faster in high mortality than moderate mortality. All three species will likely be important to future forest in areas with high mortality, and lodgepole pine will play a substantial role. In contrast, in moderate mortality areas lodgepole pine regeneration is nearly absent and spruce and fir are growing fastest. Here the forest understory will be made up of shade tolerant species, and the forest will become progressively more dominated by these species as this stratum develops.
Keywords: aspen; bark beetles; lodgepole pine; mountain pine beetle; subalpine fir; Engelmann spruce